By applying the Quotient Rule of Exponents, we can subtract the exponents to get an equivalent form:
2^8 ÷ 2^4 = 2^(8-4) = 2^4.
Therefore, an equivalent form of 2^8 ÷ 2^4 is 2^4.
Using the Quotient Rule of Exponents, what is an equivalent form of 2^8÷2^4 ?(1 point)
17 answers
using the Quotient Rule of Exponents, what is the exponent in an equivalent form of 7^9/7^6 if the base is 7?(1 point)
Using the Quotient Rule of Exponents, when dividing two numbers with the same base, we subtract the exponents:
7^9/7^6 = 7^(9-6) = 7^3.
Therefore, the exponent in an equivalent form of 7^9/7^6, when the base is 7, is 3.
7^9/7^6 = 7^(9-6) = 7^3.
Therefore, the exponent in an equivalent form of 7^9/7^6, when the base is 7, is 3.
Using the Power Rule of Exponents, what is an equivalent form of the expression (3^5)^2 ?(1 point)
Using the Power Rule of Exponents, when raising a power to another power, we multiply the exponents:
(3^5)^2 = 3^(5*2) = 3^10.
Therefore, an equivalent form of the expression (3^5)^2 is 3^10.
(3^5)^2 = 3^(5*2) = 3^10.
Therefore, an equivalent form of the expression (3^5)^2 is 3^10.
Using the Power Rule of Exponents, what is an equivalent form of the expression (6^3)^3 ?(1 point)
Using the Power Rule of Exponents, when raising a power to another power, we multiply the exponents:
(6^3)^3 = 6^(3*3) = 6^9.
Therefore, an equivalent form of the expression (6^3)^3 is 6^9.
(6^3)^3 = 6^(3*3) = 6^9.
Therefore, an equivalent form of the expression (6^3)^3 is 6^9.
Using the Power Rule of Exponents, what is an equivalent form of the expression (5^6)^2 ?(1 point)
Using the Power Rule of Exponents, when raising a power to another power, we multiply the exponents:
(5^6)^2 = 5^(6*2) = 5^12.
Therefore, an equivalent form of the expression (5^6)^2 is 5^12.
(5^6)^2 = 5^(6*2) = 5^12.
Therefore, an equivalent form of the expression (5^6)^2 is 5^12.
as a whole mumner
As a whole number, 5^12 cannot be simplified further. It remains as 5^12.
Using the Power Rule of Exponents, what is the whole number exponent in an equivalent form of (5^6)^2 ? (1 point)
Using the Power Rule of Exponents, when raising a power to another power, we multiply the exponents:
(5^6)^2 = 5^(6*2) = 5^12.
Therefore, the whole number exponent in an equivalent form of (5^6)^2 is 12.
(5^6)^2 = 5^(6*2) = 5^12.
Therefore, the whole number exponent in an equivalent form of (5^6)^2 is 12.
Using the Power Rule of Exponents, what is the whole number exponent in an equivalent form of (2^7)^4 ? (1 point)
Using the Power Rule of Exponents, when raising a power to another power, we multiply the exponents:
(2^7)^4 = 2^(7*4) = 2^28.
Therefore, the whole number exponent in an equivalent form of (2^7)^4 is 28.
(2^7)^4 = 2^(7*4) = 2^28.
Therefore, the whole number exponent in an equivalent form of (2^7)^4 is 28.
Evaluate the expression (1^4 x (5+3)/(6−2))^2 . Show all your work.
To evaluate the expression (1^4 x (5+3)/(6−2))^2, we need to follow the order of operations and simplify step by step.
First, let's simplify the expression inside the parentheses:
5 + 3 = 8
6 - 2 = 4
So, the expression becomes: (1^4 x 8/4)^2
Next, let's simplify the exponent:
1^4 = 1
Now, we can substitute the simplified values back into the expression:
(1 x 8/4)^2
Next, let's simplify the multiplication and division:
8/4 = 2
So, the expression now is: (1 x 2)^2
Next, let's simplify the exponent:
(1 x 2)^2 = 2^2 = 4
Therefore, the evaluation of the expression (1^4 x (5+3)/(6−2))^2 is 4.
First, let's simplify the expression inside the parentheses:
5 + 3 = 8
6 - 2 = 4
So, the expression becomes: (1^4 x 8/4)^2
Next, let's simplify the exponent:
1^4 = 1
Now, we can substitute the simplified values back into the expression:
(1 x 8/4)^2
Next, let's simplify the multiplication and division:
8/4 = 2
So, the expression now is: (1 x 2)^2
Next, let's simplify the exponent:
(1 x 2)^2 = 2^2 = 4
Therefore, the evaluation of the expression (1^4 x (5+3)/(6−2))^2 is 4.